Use and rationale for taking nutritional supplements among collegiate athletes at risk for nutrient deficiencies - Kiertscher, E.; DiMarco, N. M. (Performance Enhancement & Health, 2013)
This study examined aspects of collegiate athletes` eating habits, weight, and their use and perception of nutritional supplements. The purpose of this study was to determine if athletes at risk for nutrient deficiencies use nutritional supplements, and if their concerns about positive drug tests discouraged their use of nutritional supplements. This study examined 134 athletes from collegiate universities across the United States. They answered a questionnaire, developed by the researchers through Psychdata. From the athletes` responses to questions about their eating habits, the study categorized participants into two groups: athletes at risk for nutrient deficiencies and athletes not at risk for nutrient deficiencies.